Autistic Traits in the Neurotypical Population do not Predict Increased Response Conservativeness in Perceptual Decision Making. (October 2018) - Pirrone, Angelo; Wen, Wen; Li, Sheng; Baker, Daniel H.; Milne, Elizabeth
Recent research has shown that adults and children with autism spectrum disorders have a more conservative decision criterion in perceptual decision making compared to neurotypical individuals, meaning that autistic participants prioritise accuracy over speed of a decision. Here, we test whether autistic traits in the neurotypical population correlate with increased response conservativeness. We employed three different tasks; for two tasks we recruited participants from China ( N  = 39) and for one task from the United Kingdom ( N  = 37). Our results show that autistic traits in the neurotypical population do not predict variation in response criterion. We also failed to replicate previous work showing a relationship between autistic traits and sensitivity to coherent motion and static orientation. Following the argument proposed by Gregory and Plaisted-Grant, we discuss why perceptual differences between autistic and neurotypical participants do not necessarily predict perceptual differences between neurotypical participants with high and low autistic traits.